Tubridge flow-diverting stent for treatment of unruptured intracranial complex aneurysms - Juan, Bao; Zhang, Xian; Cao, Yi (Frontiers in Neurology, 2025)
ObjectiveTo investigate the efficacy and safety of the Tubridge flow diverter (TFD) in treating unruptured intracranial complex aneurysms.MethodsA retrospectively was performed on consecutive patients with unruptured intracranial complex aneurysms treated with TFD at our institution between October 2019 and December 2022. Clinical data, including demographic characteristics, angiographic findings, and follow-up outcomes, were collected to assess postoperative and follow-up aneurysm occlusion rates. Complications and clinical outcomes were evaluated, with favorable outcomes defined as a modified Rankin Scale (mRS) score of 0–2.ResultsA total of 72 patients harboring 75 aneurysms were included, with 47 aneurysms treated with TFD alone and 28 undergoing combined TFD and coiling. Fifty-six aneurysms in 53 patients underwent at least one digital subtraction angiography (DSA) examination. The median follow-up duration at the final visit was 156.00 days, yielding a successful aneurysm occlusion rate of 78.57% (44/56) and a median time to occlusion of 139.00 days. The complete occlusion rate was significantly higher in non-saccular aneurysms (92.86%, 13/14) than in saccular aneurysms (64.29%, 27/42). Severe stenosis (>50%) occurred in 3 of 55 stents (5.45%). Among 67 patients (5 lost to follow-up), 4 ischemic and 8 hemorrhagic complications were recorded, with 97.01% of patients achieving an mRS score of 0–1.ConclusionSmall-to-medium-sized aneurysms (maximum diameter <10 mm) can be effectively managed with TFD alone. TFD demonstrates minimal impact on branch vessels, and patients with mild in-stent stenosis may be monitored without intervention. The TFD is safe and effective for treating various types of unruptured intracranial complex aneurysms.